The banking system in Korea - Chuh, Eun Shik.; The Bank of Korea (Seoul : The Bank of Korea, 1969)
This edition, "The banking system in Korea", reviews and clarifies the historical development and presents structure and function of banking institutions in Korea, which have contributed to the rapid economic development. It attempts to present in brief the important functions of the Korean monetary structure.
rpm 10/05/2018
Loans
Keywords: Banks and Banking; Korea